ASSESSMENT THE INFLUENCE OF PATIENT COUNSELING ON QUALITY OF LIFE IN TYPE-II DIABETES MELLITUS PATIENTS. - SOURAV GHOSH; AJEET KUMAR RAJVANSHI; SHRI KISHUN (International Journal of Pharma and Bio Sciences, 2010)
This study was carried out to assess the influence of patient counseling on patients perception about the disease management and quality of life in type II diabetes mellitus patients. A randomized controlled study was carried out over a period of forty five days in medicine department of S.D medical Hospital, Uttar Pradesh, India. A total of 22 patients were taken, out of them 72% was male and 28% was female. The patients were distributed into two groups (Control and test) and where each group was contained nine patients. Our study showed that Patients with type II diabetes mellitus of age above50 years (77.8%) was predominant than age below 50 years (22.2%)and diabetic history of onset of diabetes above 10 years (77.7%) was more than those with the age of 10 years (22.2%) below. The control value of Fasting Plasma Glucose level (FPG) and Postprandial Plasma Glucose level (PPG) was reduced significantly upto 180± 2.597 (p<0.05) and 194± 2.596 (p<0.01) respectively after 45 days of patient follow up. The result of the study suggest that community-based patient counseling regarding Disease, medication and Life style modification for type 2 diabetic patients, can be effectively implemented in developing nations and that important health indicators significantly improve.